Using Lebanon's Large Capital Inflows to Foster Sustainable Long-Term Growth - World Bank (World Bank, 2012)
This report aims to provide a diagnostic of the Lebanese economy and policy advice to a broad audience. To that effect, an analysis of the dynamics of foreign inflows and of the economy over the past decades is undertaken. Specifically, this report attempts to provide a vision for where would Lebanon be in 15 to 20 years if needed structural reforms are implemented. This report provides a quantification of the growth impact of these reforms, taken individually or combined. By doing so, it gives both an indication on the opportunity costs of not reforming and provides a vision on what the development stage could be in Lebanon in 15 to 20 years if reforms are implemented. The report includes a set of econometric simulations and analysis aiming: 1) to establish the relation between the dynamic of foreign financial inflows and deposits over a period of 20 years, 2) to establish the relation between deposits as proxy for foreign financial inflows from one side; and oil price as proxy for regional wealth, macroeconomic and security stability, and policy variables from the other side and, 3) to estimate the relation between economic fluctuations from one side; and bank lending as one of the channels of transmission of foreign financial inflows, and debtor interest rate from the other side.